EFECTOS DEL ESTRÉS LABORAL POST PANDEMIA EN TRABAJADORES DE UNA EMPRESA DEL SECTOR COMERCIAL EN LA CIUDAD DE BOGOTÁ - Juliana Sierra; Eliana Rodríguez; Laura Vargas; Gina Fuentes (Revista Ingeniería, Matemáticas y Ciencias de la Información)
During the COVID-19 pandemic, the global working population presented excessive work overload due to the increase inresponsibilities to be executed, the lack of compliance with disconnection schedules and the imbalance in relation to routinefamily activities, developed in the same hours, generating a perception of high levels of work stress. This research aims toanalyze the symptoms associated with work stress and its relationship with the musculoskeletal symptoms of workers in acompany in the commercial sector. This study corresponds to a non-experimental, observational cross-sectional investigation,based on a mixed-type research approach by having a collection of qualitative and quantitative information, the scope isdescriptive since the affectation of work stress on the health of workers was analyzed. post-pandemic workers. Thesymptomatology associated with work stress in the surveyed population is mainly related to neck and/or back pain,according to the results of the applied survey. For the section on musculoskeletal discomfort, the parts of the body mostaffected were the neck, shoulder, and lower back, which indicates that the relationship between symptomatology due tostress corresponds only to muscle tension and no consequences are found for associated health disorders to stress.